Efektivitas Aplikasi e-SIDAK dalam Penilaian Kinerja PNS di BKPSDM Kabupaten Belitung - Risnu Pratama; Ardieansyah, Ardieansyah; Agung Nurrahman (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effectiveness of the e-SIDAK application as a tool for recording and evaluating the performance of civil servants at BKPSDM Belitung Regency. The research employs a descriptive qualitative approach with 12 purposively selected informants, including managers, administrators, and application users. Data were collected through semi-structured interviews, observations, and documentation, and analyzed thematically using NVivo 12 Pro based on the digital service effectiveness indicators proposed by Pedrosa et al., namely ease of use, simplicity, understandability, consistency, trustworthiness, availability, speed, and usefulness. The findings indicate that the e-SIDAK application fulfills most effectiveness indicators, particularly in terms of ease of use, process simplicity, clarity of information, interface consistency, and service usefulness. The application facilitates systematic work activity recording, simplifies reporting, improves employee discipline, and supports performance monitoring integrated with the employee performance allowance system. However, its effectiveness remains limited in terms of system reliability, service availability, and access speed due to server capacity constraints, network conditions, and the accumulation of data input at the end of reporting periods. In addition, the point-based evaluation system has not fully reflected task duration, complexity, and workload. This study recommends strengthening system infrastructure, developing user guidelines, regulating input timing, and improving the point-based evaluation system to enhance digital service effectiveness in local government institutions.